Membangun Ketahanan Pangan Untuk Pencegahan Stunting Di Desa Tananagaya Kecamatan Mamosalato Kabupaten Morowali Utara Sulawesi Tengah - Rinto Z.W Abidjulu; Sepryanus Rano Putra; Mikhael Jibrael Balo; Feliks Arfid Guampe; Rian Djalo’e; Novita Sari Sanco’o; Jein Toii; Agnes Terampe; Deslin Timbaroa; Anggi Gito Monolimay; Alseb Buande; Join Hengkeng (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Stunting is a condition of growth failure that occurs in children due to chronic malnutrition, malnutrition in children can occur starting from the womb to children aged 2 years. After the child is 2 years old, the incidence of stunting can only be seen. Building food security is one of the important steps in efforts to prevent stunting in Tananagaya Village with methods that include several stages, planning, organizing, actuating, and controlling. Based on the results of the programs that have been carried out, food security is an important element in preventing stunting. Therefore, it is necessary to improve food security to prevent stunting and improve the welfare of the people of Tananagaya village.